THE INFLUENCE OF PRODUCT QUALITY, SERVICE QUALITY, AND SATISFACTION AS IMPORTANT FACTORS IN CUSTOMER LOYALTY AT AYAM GORENG PAK CIPTO BANYUANYAR - Akbar Adi Nugroho; Lukman Hakim (Universitas PGRI Semarang, 2025)
Customer loyalty is essential for the sustainability of culinary enterprises, particularly traditional small and medium-sized enterprises (SMEs) that rely significantly on repeat purchases. The purpose of this study is to investigate how customer loyalty is impacted by the quality of products and services, while also assessing the pivotal role of customer satisfaction in enhancing loyalty. Utilizing a quantitative research methodology, the study employed a survey design. The target population consisted of patrons of Ayam Goreng Pak Cipto Banyuanyar, with a total of 100 respondents selected through purposive sampling based on their experience of at least three purchases. Data were gathered through Partial Least Squares (PLS) analysis was performed on structured surveys technique to assess both measurement and models of structure. The results indicate that product quality and customer satisfaction have a positive effect on customer loyalty, with customer satisfaction identified as the most influential variable. Conversely, In this case, loyalty is not directly impacted by service quality specific context. These findings suggest that traditional culinary enterprises should focus on sustaining consistent product quality and enhancing the overall customer experience to bolster loyalty.